Ingen nöd utan lag - En undersökning av förutsättningarna för att under åberopande av nöd avvärja fara mot allmänna intressen - Bentelius,Johanna (2025)
In this paper a dogmatic approach has been used in examining the conditions for an individual to protect a public interest under the state of necessity in the Swedish Criminal Code. The state of necessity has evolved from solely protecting the individual and their property to also providing protection for public interests. According to the legislative history, a state of necessity to avert danger to public interests should only be applicable in rare exceptional cases. It is also not for private individuals to intervene in matters that are the responsibility of authorities, except if there’s special reasons and the interest is of exceptional importance. Earlier rulings addressing actions by individuals aimed at protecting a public interest under the state of necessity has not been entirely consistent, and the boundaries do not appear to be entirely clear. The rulings have, however, been consistent in the treatment that a state of necessity cannot exist if the interest in question is already regulated or intended to be regulated in legislation or by public authorities. This circumstance has amounted to the assessment that no state of emergency exists. Two recent rulings have partly deviated from this earlier interpretation. In NJA 2017 p. 872, the Supreme Court held that a state of emergency existed because there was a danger to a protected interest. In the defence assessment, it was then noted that the balancing of interests had already been done in legislation, and therefore the act was not considered justified. In NJA 2023 p. 1057, the Supreme Court stated that the climate crisis may constitute a state of emergency in accordance with the regulation. However, the Court held that the act must contribute in a “reasonably concrete and immediate way” in protecting the interest. Considering the new assessments in these two recent cases, the following has emerged regarding the conditions for an individual to, under the state of necessity, avert a danger to a public interest. The act of necessity must align with the balancing of interests carried out by public authorities, and the public interest must be of exceptional importance. The state of emergency may be long-lasting, but the act must contribute in a reasonably concrete and immediate way to saving the interest in question. The conditions for invoking the state of necessity to protect public interests can be seen in light of the fact that the state of necessity has a long history as a natural law principle for individuals to safeguard their own interests in exceptional situations. The inclusion of public interests is relatively new and is dependant of partly different considerations.
Keywords: straffrätt; nödrätt